INDICATING THE VALUE OF ISLAMIC EDUCATION THROUGH SILAT BEKSI IN YOUTH IN THE VILLAGE OF SILAT PETUKANGAN UTARA, SOUTH JAKARTA - Rina Kurnia; Achmad Muhajir; Eddy Saputra (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This research aims to analyze the role of Silat Beksi in strengthening character education for teenagers in Kampung Silat Petukangan Utara, South Jakarta. Silat Beksi is an Indonesian cultural heritage that contains high moral and ethical values. This research uses a qualitative approach by collecting data through interviews, observation, and document analysis. The research results show that Silat Beksi has great potential for shaping the character of teenagers. Through the practice of Silat Beksi, teenagers can develop values such as discipline, a sense of responsibility, hard work, and appreciation for local cultural values and traditions. Apart from that, Silat Beksi also promotes a sense of solidarity and leadership, which are important in developing the character of teenagers. This study emphasizes the importance of supporting and expanding the Silat Beksi program in the North Petukangan Silat Village environment as an integral part of youth character education. This involves collaboration between the school, the Silat Beksi community, and the local government to ensure that the values and skills taught by Silat Beksi continue to be applied in the daily lives of teenagers.